1988
DOI: 10.1073/pnas.85.18.6622
|View full text |Cite
|
Sign up to set email alerts
|

A highly conserved repetitive DNA sequence, (TTAGGG)n, present at the telomeres of human chromosomes.

Abstract: A highly conserved repetitive DNA sequence, (TTAGGG)., has been isolated from a human recombinant repetitive DNA library. Quantitative hybridization to chromosomes sorted by flow cytometry indicates that comparable amounts of this sequence are present on each human chromosome. Both fluorescent in situ hybridization and BAL-31 nuclease digestion experiments reveal major clusters of this sequence at the telomeres of all human chromosomes. The evolutionary conservation of this DNA sequence, its terminal chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
1,270
1
28

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,056 publications
(1,315 citation statements)
references
References 33 publications
16
1,270
1
28
Order By: Relevance
“…1,2 It has been demonstrated that telomeres became shorter after cell division, and that cells show growth arrest when telomere length reaches a critical point. [3][4][5] Telomerase, a ribonucleoprotein enzyme, synthesizes telomeric repeats at the ends of chromosomes to maintain telomere length.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It has been demonstrated that telomeres became shorter after cell division, and that cells show growth arrest when telomere length reaches a critical point. [3][4][5] Telomerase, a ribonucleoprotein enzyme, synthesizes telomeric repeats at the ends of chromosomes to maintain telomere length.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although the sequence of these terminal structures varies among different organisms, all telomeres are composed of large arrays of short guaninerich sequences, such as those found in mammalian cells, 5 0 -TTAGGG-3 0 . 3,4 In addition to these repeated sequences, a number of proteins populate the mammalian telomere and serve to regulate telomere structure. 5 The structurally related telomeric repeat binding factor 1 (TRF1) and TRF2 proteins bind double-stranded telomeric DNA and play important roles in regulating the telomere length.…”
mentioning
confidence: 99%
“…Telomeres comprise of tandem arrays of (TTAGGG)n repeats in most eukaryotes (Moyzis et al, 1988). Telomeres serve as protective caps that prevent chromosomes from fusing together and causing DNA rearrangements that can lead to karyotypic changes and genomic instability (Greider, 1991).…”
mentioning
confidence: 99%